Chemical kinetics method for evaluating the thermal stability of Organic Rankine Cycle working fluids. (5th May 2016) - Dai, Xiaoye; Shi, Lin; An, Qingsong; Qian, Weizhong
Highlights: A chemical kinetics method for evaluating the thermal stability of ORC working fluids. An experimental system to obtain the apparent kinetic parameters. An apparent chemical kinetics model to predict the thermal stability. The n-pentane pre-exponential factor was 7.5275 × 10 12 s −1 and the activation energy was 227.57 kJ/mol. Graphical Abstract: Abstract: Organic Rankine Cycle (ORC) systems are widely used to generate electricity with industrial waste heat and renewable energy. Transcritical ORCs with high temperature heat sources are more attractive than subcritical ORCs due to their lower exergy losses, higher thermal efficiencies and higher work outputs. The working fluid thermal stability is the primary consideration in the working fluid selection due to decomposition at high temperatures. This paper presents a chemical kinetics method for evaluating the thermal stability of ORC working fluids. A chemical kinetics experimental system was built with n-pentane as the test working fluid. The influences of pressure and temperature were analyzed experimentally and theoretically. An apparent chemical kinetics model was established to predict the thermal stability with the apparent kinetic parameters of n-pentane measured experimentally. This apparent chemical kinetics model gives significant guidance for the working fluid selection and ORC system design.